The Nanoscale Structure of Human Female Osteoporotic Bone Investigated by Transmission Electron Microscopy - Strakhov, Ivan (My University, 2019)
Bone is a complex hierarchical biomaterial constantly undergoing remodeling events initiated by cell signaling and fulfilled by migratory bone cells. In osteoporosis, a multitude of signaling factors cause bone resorption to proceed quicker than bone reformation, resulting in a lower bone mineral density (BMD) and porosity as seen by thinning of the cortex and trabeculae. However, the structural motifs of these altered regions of the skeleton have not been understood on the nanoscale. In this thesis, transmission electron microscopy (TEM) was used with an image analysis technique termed nanomorphometry, developed to enable the measurement of nanoscale structural features in human bone. Several nanoscale bone quality bioindicators relevant to the collagen fibrils and bone mineral (mineral lamellae, ML) components were defined and tested (collagen fibril diameter, interfibrillar spacing, ML thickness & ML stack thickness) among two donor cohorts of post-menopausal osteoporotic female patients and age- and sex-matched controls. In one cohort, the anatomical region investigated was the intertrochanteric crest of the femur, while in the second, the femoral neck was studied. The bone sections were prepared using an ion milling workflow yielding electron-transparent views of the bone ultrastructure. Blinded image analysis of the ultrastructure revealed that in both cohorts, the thickness of the MLs was significantly larger in osteoporotic samples versus their controls. In the former cohort, it was found that anti-resorptive drug use in the treated group did not return the ML thickness back to control levels. In the latter cohort, the ML thickness correlated more closely with the proximal femur bone mineral density (BMD) than the age of the patient. These findings suggest that the morphology of the nanoscale mineral phase is affected by osteoporosis, an effect indirectly observed by other techniques, and warrants further exploration into the implications of this effect on bone quality, fragility and strength.
Bioindicators of the nanoscale structural quality of bone were investigated using ion milling and transmission electron microscopy of osteoporotic bone from human female donors.
Keywords: Bone; Osteoporosis; Transmission Electron Microscopy; Ion Milling; Biomaterials; Ultrastructure; Fracture; Image Analysis